2021
DOI: 10.1063/5.0043062
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing weak magnetic field MME coupling in NdFeB magnet/piezoelectric composite cantilevers with stress concentration effect

Abstract: In this work, we theoretically and experimentally report a NdFeB magnet/piezoelectric composite cantilever with varying stiffness for enhancing magneto-mechano-electric (MME) coupling under weak AC magnetic field Hac excitation. Measurement results show that the MME composite cantilever can produce a relatively high peak-peak output power of 12.8 mW and a peak-peak current of 0.735 mApp under Hac = 7 Oe at a resonance frequency of 36 Hz. Even when Hac is as low as 0.2 Oe, equivalent to the level of the earth m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Nevertheless, it should be noted that in [35][36][37][38][39][40][41][42][43][44][45][46][47][48] measurements were carried out either at a higher resonance frequency, ranging from units to tens of kHz, or far from resonance. We are aware of only two works [4,5] in which the magnitude of the ME effect at a similarly low resonance frequency exceeded the values of α we obtained.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Nevertheless, it should be noted that in [35][36][37][38][39][40][41][42][43][44][45][46][47][48] measurements were carried out either at a higher resonance frequency, ranging from units to tens of kHz, or far from resonance. We are aware of only two works [4,5] in which the magnitude of the ME effect at a similarly low resonance frequency exceeded the values of α we obtained.…”
Section: Discussionmentioning
confidence: 51%
“…To the best of our knowledge, the lowest reported fundamental bending resonance frequency of 27.8 Hz was achieved in ME sensors using the thin-film approach by direct spin coating of polyvinylidene fluoride-trifluoroethylene (PVDF-TrFE) onto a Metglas substrate [4]. A NdFeB magnet/piezoelectric composite cantilever with varying cross sections demonstrated a bending resonance frequency of 29 Hz and a high value for its ME voltage coefficient (≈500 V/A) [5]. A low resonance frequency in [5] was realized by employing a NdFeB permanent magnet as a tip mass.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] It has been a challenge to continuously power those individual wireless sensors and the related electronic components in WSNs, because conventional batteries have their shortcoming of the finite lifetime. [7] Therefore, it becomes a promising and feasible approach to harvest energy from environmental energy source, including vibrational energy, [8,9] wave energy, [10] stray magnetic energy, [11,12] solar energy, [13] etc., to power these individual wireless sensor (as self-powered sensors). [7] The low-amplitude, low frequency stray magnetic field is widely surrounding in or around the modern building, generated by power supply cables and air conditioning machines et al; [5,7,14] while the vibrational energy coming from vehicle motions, human walking, and machines are also widespread in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Our group reported a NdFeB magnet/piezoelectric composite cantilever with varying stiffness for weak magnetic field H ac energy harvesting, and we found that a weak H ac of as low as 0.2 Oe could be still strong enough to drive four LEDs lighting. [12] Lim et al [6] proposed a magneto-mechano-triboelectric nanogenerator (MMTEG) combining triboelectric effect with magnetic force-torque effect, realizing maximum peak power of 21.8 mW under H ac = 7 Oe. [6] Currently, researches in energy harvesting field mainly focus on the improvements in composite materials and structures, and/or the introduction of new physical mechanism.…”
Section: Introductionmentioning
confidence: 99%